Teaching Economic Inequality and Capitalism in Contemporary America (Springer International Publishing, 2018)
This book discusses pedagogical solutions that enable students to see how capitalist processes and economic inequalities intersect and shape our assumptions and behaviours. The contributors provide thoughtful reflections on the struggles and opportunities instructors face in teaching about these topics while competing against the invisibility of capitalist forces and prevalent social myths, such as "anyone who works hard can achieve". This book will not only help instructors empower students to recognize economic injustice and its interaction with capitalist organization, but also develops and acts on transformative solutions. Through analysis of the classed dimensions of the current political, economics, and cultural climate, as well as presenting novel lesson plans and classroom activities, this book is of great value for college and university professors.